480 Preoperative Templating in Hip Hemiarthroplasty Improves Femoral Offset and Function. (4th May 2021) - Saleem, S; Parikh, S; Parratt, T; Loeffler, M
Abstract: The use of preoperative templating for hip hemiarthroplasty increases the likelihood of successfully restoring offset. This study sought to identify whether templating improves radiographic and clinical outcomes in this group. Data belonging to all patients that underwent hip hemiarthroplasty between March 2018 and March 2019 were collected. The patients were grouped based on whether or not their preoperative images were templated. Radiographs were studied retrospectively to calculate preoperative and postoperative offset and LLD for each patient. The clinical outcomes that were measured included the rate of periprosthetic fracture, dislocation and contra-lateral neck of femur fracture for each group. Data was analysed by SPSS. There were 208 patients of which 72 were templated and 136 not templated. The percentage difference between the preoperative and postoperative offset was lower in the templated group (p < 0.05). There was no significant difference in radiographic LLD between the two groups. There was no significant difference in the clinical outcomes between the two groups. A significantly closer restoration to the original offset was achieved with preoperative templating, which is likely to improve function in this group. There were no significant differences in the other clinical outcomes between the two groups.